2009
DOI: 10.1016/j.ydbio.2009.02.019
|View full text |Cite
|
Sign up to set email alerts
|

foxD5 plays a critical upstream role in regulating neural ectodermal fate and the onset of neural differentiation

Abstract: foxD5 is expressed in the nascent neural ectoderm concomitant with several other neural-fate specifying transcription factors. We used loss-of-function and gain-of-function approaches to analyze the functional position of foxD5 amongst these other factors. Loss of FoxD5 reduces the expression of sox2, sox11, soxD, zic1, zic3 and Xiro1-3 at the onset of gastrulation, and of geminin, sox3 and zic2, which are maternally expressed, by late gastrulation. At neural plate stages most of these genes remain reduced, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
160
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(181 citation statements)
references
References 72 publications
19
160
2
Order By: Relevance
“…Expansion of Zic2 leads to the inhibition of Xngnr-1, which normally induces expression of Myt-1 and Delta-1 to promote neurogenesis (Bellefroid et al, 1996;Brewster et al, 1998;Chitnis et al, 1995). Geminin plays a primary role in maintaining neuroectoderm in an 'immature state', conferring a reduced response to differentiation signals (Neilson et al, 2012;Yan et al, 2009;Yan et al, 2010). Geminin is highly expressed in proliferating neural progenitors (Spella et al, 2007), where it interacts with Brahmarelated gene 1 to inhibit neuronal differentiation and increase proliferation (Seo et al, 2005a;Seo et al, 2005b).…”
Section: Erf or Etv3/3l Knockdown Expand Expression Of Neural Progenimentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion of Zic2 leads to the inhibition of Xngnr-1, which normally induces expression of Myt-1 and Delta-1 to promote neurogenesis (Bellefroid et al, 1996;Brewster et al, 1998;Chitnis et al, 1995). Geminin plays a primary role in maintaining neuroectoderm in an 'immature state', conferring a reduced response to differentiation signals (Neilson et al, 2012;Yan et al, 2009;Yan et al, 2010). Geminin is highly expressed in proliferating neural progenitors (Spella et al, 2007), where it interacts with Brahmarelated gene 1 to inhibit neuronal differentiation and increase proliferation (Seo et al, 2005a;Seo et al, 2005b).…”
Section: Erf or Etv3/3l Knockdown Expand Expression Of Neural Progenimentioning
confidence: 99%
“…Primary neurogenesis is preceded by neural induction, which requires inhibition of bone morphogenetic protein (BMP) signaling (Wills et al, 2010;Wilson and Hemmati-Brivanlou, 1995) together with active fibroblast growth factor (FGF) signaling (reviewed by Dorey and Amaya, 2010;Marchal et al, 2009;Wills et al, 2010). Neural induction leads to the expression of proproliferative and neural-fate stabilizing transcription factors such as Foxd4l1, Geminin, Sox2/3 and Zic-family genes (Branney et al, 2009;Marchal et al, 2009;Yan et al, 2009). The concerted action of these genes promotes proliferation and maintenance of immature neural precursors.…”
Section: Introductionmentioning
confidence: 99%
“…1B). Previous studies reported that FoxD5a played (Yan et al, 2009a). However, the function of FoxD5b, a putative pseudo-allele gene of FoxD5a, has not yet been studied.…”
Section: Resultsmentioning
confidence: 98%
“…Later, the XFLIP has been classified into sub-families, termed XFD-12, XFD-12' and XFD-12" (Solter et al, 1999). It has been shown that FoxD5a is involved in the initiation of neural induction, but not in neuronal differentiation (Neilson et al, 2012, Yan et al, 2009a, Yan et al, 2009b, Yu et al, 2002. Recently, Neilson et al, dem-onstrated that FoxD5 regulates the transition of neuroectoderm via controlling a network of genes (Neilson et al, 2012).…”
mentioning
confidence: 99%
“…The FoxD5 can keep the neural ectoderm in undifferentiated stage after neural induction (Sullivan No (Yan et al, 2009a), gem and zic2 (Yan et al, 2009b). Experiments results suggested that the maintenance of FoxD5 expression requires bFGF, Wnt and Nodal signaling (Fetka et al, 2000).…”
Section: Introductionmentioning
confidence: 99%